ANALISIS KESULITAN BELAJAR PADA MATA PELAJARAN SOSIOLOGI SISWA DI MAS MINHAJUL AMILIN - Afrianti, Lis; Rustiyarso, Rustiyarso; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis research goals to know the students' learning difficulties in class XI on subjects sociology seen from internal factors, external factors and the efforts of teachers to overcome the problem of learning difficulties. The approach used qualitative approach with descriptive methods. This study uses 5 informants. The results showed students' learning difficulties from internal factors of observations and interviews to students note that the students showed the causes of learning difficulties that come from within them, such as having an attitude of learning, motivation, concentrating poor. Less able to demonstrate learning achievement, lack of confidence and poor study habits. Of external factors, family and school environment, lack of supervision and attention from their parents as well as the lack of availability of supporting infrastructure in the learning process causing the child into learning difficulties. The efforts of teachers in overcoming learning difficulties already showed results. Seen from the value obtained by the students after the teacher did stage treatment can reach values minimum completeness (KKM).Keywords: Students"™ Difficulties of Studying, TeacherEffort, The Causes